Evaluation of the health of the Bunche mangrove ecosystem using halophilic bacteria as bioindicators (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Mangroves are highly productive coastal ecosystems whose microbial communities are influenced by environmental and anthropogenic factors. In the province of Esmeraldas, particularly in the community of Bunche, shrimp farming activities and the discharge of untreated wastewater have altered the biodiversity of sediments. The main objective of this study was to assess the health of the mangrove ecosystem through the phenotypic and genotypic characterization of cultivable halophilic bacteria, with an emphasis on their potential as environmental bioindicators. Sediment samples were collected from four sampling sites, physicochemical parameters were measured, and bacteria were isolated using media with different NaCl concentrations. The strains were morphologically characterized, Gram-stained, and subjected to 16S rRNA gene sequencing. Preliminary results suggested the presence of bacteria with high salinity tolerance and potential resistance to sodium metabisulfite. It was concluded that these bacterial communities represent a valuable tool for assessing the environmental quality of mangroves and can be used as bioindicators of salinity and pollution.